Change in serum TSH levels within the reference range was associated with variation of future blood pressure: a 5-year follow-up study - Jiang, F; Liu, A; Lai, Y; Yu, X; Li, C; Han, C; Zhang, Y; Wang, X; Wang, Z; Bao, S; Lv, N; Jin, M; et al. (Journal of human hypertension, 2017)
Controversy exists on the relationship between serum thyrotropin (TSH) and blood pressure, and only a few prospective studies are available up to now. The study aimed to investigate the association between serum TSH within the reference range and blood pressure through a 5-year follow-up study. A total of 623 subjects with normal TSH were followed up for 5 years, including the measurement of demographic data, blood pressure, height, weight and serum TSH. Finally, 531 subjects were included in this prospective study. Body mass index (BMI), prevalence of hypertension, and systolic and diastolic blood pressure were all higher at follow-up than at baseline. Adjusted for age, gender, smoking status, BMI and homoeostasis model assessment of insulin resistance (HOMA-IR) at baseline, multiple linear regression analyses found no relationship between serum TSH at baseline and levels of blood pressure at follow-up, but the changes in serum TSH levels during follow-up was positively associated with the changes in systolic blood pressure ( B =2.134, P <0.05), which became more significant in women but not significant in men. The change of systolic blood pressure in group of TSH increase >0.5 mIU l −1 was significantly higher than in group of TSH decrease >0.5 mIU l –1 within reference, after adjusting for age, gender, smoking status, BMI and HOMA-IR at baseline. This result became more significant in women, but no statistical significance was observed in men. Co-variation with serum TSH levels and blood pressure was observed during 5-year follow-up among people with normal TSH.